Urban security and crime prevention in smart cities: a quantitative systematic review - Delgado, Gerard Vivo (International e-journal of criminal sciences, 2020)
The scientific literature on crime prevention in urban contexts is very vast, nevertheless it is still limited in the Smart Cities context. With the aim of assessing how this phenomenon has been studied to date from an evidence-based approach, a quantitative systematic review has been conducted on the basis of gathering information from the most recent scientific literature (2014-2019) on strategies for improving urban safety in smart city scenarios. Specifically, it was systematised according to different variables such as research designs, results of the implementation of measures to improve urban safety, crimes assessed, fields of application of the measures and problems associated with the use of these measures. As a result, most of the studies examined are of a cross-sectional, non-experimental nature. Also, most results are descriptive, and the preventive measures evaluated have positive effects. Similarly, most of the applications are connected with civil, preventive and police settings. Finally, this paper analyses the importance of following up on this emerging line of research